Review of Innovation and Efficiency of Modern Technology-Based Irrigation Systems in the Manufacturing Process - Hariandi, Yusuf; Pranoto, Hadi (Institute for Research on Innovation and Industrial System (IRIS), 2025)
Efficient and smart irrigation systems are urgently needed amid global water scarcity and pressure to increase agricultural yields. This study aims to systematically review 30 scientific journals published in the last five years that discuss modern technology-based automated irrigation systems. The study is divided into two main aspects, namely innovative aspects and efficiency aspects. The creative element covers the use of the Internet of Things (IoT), machine learning (ML), and renewable energy. Meanwhile, the efficiency aspect focuses on water conservation, energy efficiency, and increased crop yields. This research uses a systematic literature study approach by analyzing the working system, advantages, disadvantages, benefits, manufacturing processes, and equipment used. The findings show that IoT and ML-based systems excel in terms of automation and real-time adaptation, while the application of solar-based systems contributes significantly to energy sustainability. Water use efficiency reaches up to 86.6%, accompanied by a significant increase in fruit and vegetable yields. This article makes an important contribution to supporting the development of innovative and sustainability-oriented smart irrigation systems, in line with the concept of precision agriculture.